Exoproteome profiling of Trypanosoma cruzi during amastigogenesis early stages - Mandacaru, Samuel C. (PLoS One, 2019)
Chagas disease is caused by the protozoan Trypanosoma cruzi, affecting around 8 million people worldwide. After host cell invasion, the infective trypomastigote form remains 2–4 hours inside acidic phagolysosomes to differentiate into replicative amastigote form. In vitro acidic-pH-induced axenic amastigogenesis was used here to study this step of the parasite life cycle. After three hours of trypomastigote incubation in amastigogenesis promoting acidic medium (pH 5.0) or control physiological pH (7.4) medium samples were subjected to three rounds of centrifugation followed by ultrafiltration of the supernatants. The resulting exoproteome samples were trypsin digested and analysed by nano flow liquid chromatography coupled to tandem mass spectrometry. Computational protein identification searches yielded 271 and 483 protein groups in the exoproteome at pH 7.4 and pH 5.0, respectively, with 180 common proteins between both conditions. The total amount and diversity of proteins released by parasites almost doubled upon acidic incubation compared to control. Overall, 76.5% of proteins were predicted to be secreted by classical or non-classical pathways and 35.1% of these proteins have predicted transmembrane domains. Classical secretory pathway analysis showed an increased number of mucins and mucin-associated surface proteins after acidic incubation. However, the number of released trans-sialidases and surface GP63 peptidases was higher at pH 7.4. Trans-sialidases and mucins are anchored to the membrane and exhibit an enzyme-substrate relationship. In general, mucins are glycoproteins with immunomodulatory functions in Chagas disease, present mainly in the epimastigote and trypomastigote surfaces and could be enzymatically cleaved and released in the phagolysosome during amastigogenesis. Moreover, evidence for flagella discard during amastigogenesis are addressed. This study provides the first comparative analysis of the exoproteome during amastigogenesis, and the presented data evidence the dynamism of its profile in response to acidic pH-induced differentiation.